Pengaruh Ukuran Perusahaan, Proporsi Dewan Komisaris Independen, dan Kepemilikan Asing pada Pengungkapan Corporate Social Responsibility - Widyastari, Ni Kadek Widnyani; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p07, 2018)
CSRD is an important component of the company’s operation, which voluntarily contribute to the environment. This study was aimed to test and provide empirical evidence of the effect of firm size, the board of independent commissioners , and foreign ownership on CSR disclosure. This research was conducted on property and real estate companies listed on Indonesia Stock Exchange during the period of research year 2013- 2016 and the sample were 96 purposive sampling. Data analysis technique used by multiple linier regression. Based on the results of the analysis was fund that firm size had a significant positive effect on CSR disclosure. The board of independent commissioners has no significant effect on CSR disclosure. Foreign ownership has a significant negative effect on CSR disclosure. The results of this study can be a consideration for investor to invest their shares. Keywords: CSR, firm size, foreign ownership, the board of independent commissioners